miRTarBase 2020: updates to the experimentally validated microRNA–target interaction database - Huang, Hsi-Yuan; Lin, Yang-Chi-Dung; Li, Jing; Huang, Kai-Yao; Shrestha, Sirjana; Hong, Hsiao-Chin; Tang, Yun; Chen, Yi-Gang; Jin, Chen-Nan; Yu, Yuan; Xu, Jia-Tong; Li, Yue-Ming; et al. (Nucleic acids research, 2020)
Abstract MicroRNAs (miRNAs) are small non-coding RNAs (typically consisting of 18–25 nucleotides) that negatively control expression of target genes at the post-transcriptional level. Owing to the biological significance of miRNAs, miRTarBase was developed to provide comprehensive information on experimentally validated miRNA–target interactions (MTIs). To date, the database has accumulated >13,404 validated MTIs from 11,021 articles from manual curations. In this update, a text-mining system was incorporated to enhance the recognition of MTI-related articles by adopting a scoring system. In addition, a variety of biological databases were integrated to provide information on the regulatory network of miRNAs and its expression in blood. Not only targets of miRNAs but also regulators of miRNAs are provided to users for investigating the up- and downstream regulations of miRNAs. Moreover, the number of MTIs with high-throughput experimental evidence increased remarkably (validated by CLIP-seq technology). In conclusion, these improvements promote the miRTarBase as one of the most comprehensively annotated and experimentally validated miRNA–target interaction databases. The updated version of miRTarBase is now available at http://miRTarBase.cuhk.edu.cn/.